The applicability of the 1980 Hague Abduction Convention in Muslim countries: particular reference to the Malaysian position - Hamid, Abdul Ghafur@Khin Maung Sein; Abdul Hak, Nora; Mohd Zin, Najibah; Mohamed Jani, Hidayati (Brill, 2017)
In response to the increasing number of traumatic international child abduction cases, the Hague Abduction Convention (the Convention) has been adopted to secure the return of abducted children to their home country. Most Muslim countries are, however, not yet parties to the Convention. This article seeks to investigate the reason for this phenomenon, focusing in particular on the Convention’s compatibility with basic tenets of Islamic law. The article also evaluates Malaysian domestic legislation and case law in order to assess whether Malaysia is in a position to be a party to the Convention. The article finds that although there are a few areas of concern, no serious incompatibility between Shari’ah and the Convention exist, and that more dissemination is required to quash misconceptions about the Convention among Muslim countries. The article concludes with recommendations for Muslim countries in this crucial area of protecting the best interests of our children.